2010
DOI: 10.1002/gcc.20814
|View full text |Cite
|
Sign up to set email alerts
|

CKS1B amplification is a frequent event in cutaneous squamous cell carcinoma with aggressive clinical behaviour

Abstract: Genetic mechanisms giving rise to the development of cutaneous squamous cell carcinoma (cSCC) are poorly understood and development of genomic high resolution techniques has led to a better knowledge of the genetic basis of several human cancers. In this study, 16 cSCC were analyzed using array comparative genomic hybridization (arrayCGH). The most common aberrations found were gains of 3q11q13, 1q21.3q25, 13q34, and 19p13, and losses of 1p36p31, 3p24p21, 10p15q22, and 13q11q21. We detected gains (3/16) and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…31 We also examined if any DNA changes in our cases could be linked to cutaneous SCC or HPV-associated cervical and oropharyngeal carcinomas, and a summary of relevant recurring chromosomal abnormalities is shown in Supplementary Table S4. [32][33][34][35][36][37][38][39][40][41][42] Similarities include DNA gains that we observed in 3q22.3-3q28 and in 5p, as well as DNA losses in 9p, 13q, 17p, and 18q, which also are found in cutaneous SCC. 34 A smaller number of changes, which were similar in our tumors and HPV-associated neoplasms outside the eye are also listed in Supplementary Table S4.…”
Section: Discussionsupporting
confidence: 80%
“…31 We also examined if any DNA changes in our cases could be linked to cutaneous SCC or HPV-associated cervical and oropharyngeal carcinomas, and a summary of relevant recurring chromosomal abnormalities is shown in Supplementary Table S4. [32][33][34][35][36][37][38][39][40][41][42] Similarities include DNA gains that we observed in 3q22.3-3q28 and in 5p, as well as DNA losses in 9p, 13q, 17p, and 18q, which also are found in cutaneous SCC. 34 A smaller number of changes, which were similar in our tumors and HPV-associated neoplasms outside the eye are also listed in Supplementary Table S4.…”
Section: Discussionsupporting
confidence: 80%
“…In this sense, epidermal growth factor receptor (EGFR) overexpression has been associated with metastatic potential in cSCC [11], but it is also frequently found in non-metastatic cSCC and its utility as a prognostic marker is controversial [41]. CKS1B gene amplification (determined by fluorescence in situ hybridization) has also been associated with metastatic risk in cSCC [35], and we previously reported an association between the expression of epithelial to mesenchymal transition (EMT) markers and the risk of lymph node metastasis. However, we found that EMT proteins that are upregulated in the primary aggressive tumours are subsequently repressed in the metastases, which preclude their use as therapeutic targets [44].…”
Section: Discussionmentioning
confidence: 98%
“…Cks1 has been implicated in development of oral squamous cell carcinoma [131133], salivary gland tumors [106], esophageal carcinomas [80,134,135], gastric carcinoma [20,136], colorectal carcinoma [108], gall bladder carcinoma [137] and hepatocellular carcinoma [19, 138142]. Similarly Cks1 is believed to play a role in development and progression of several other types of cancers such as endometrial cancer [143], ovarian tumors [144147], prostate cancer [148], testicular cancer [149], non small cell lung carcinomas (NSCLC) [111,150], cutaneous squamous cell carcinoma [151], melanoma [15], urothelial carcinoma and renal cell carcinomas [152,153], glioblastoma and CNS tumors [154,155], head and neck carcinoma [156], fibrosarcoma [157], and myxofibrosarcoma [158]. In many of these studies there is often a distinct correlation between Cks1 expression and clinicopathologic features such as tumor grade, stage, metastasis, loss of tumor differentiation patient prognosis and cancer free survival.…”
Section: Cks1—implications In Breast and Other Cancersmentioning
confidence: 99%